The Overriding of Product Innovation, Aesthetic Value, and Social Media Marketing to Increase Consumer Purchase Intention of ‘Malangan’ Batik - Aliyyuldafa , Natasya Citra; Anjaningrum, Widiya Dewi (Institut Teknologi dan Bisnis Asia Malang, 2025)
Competition among businesses is becoming increasingly intense to create products that can increase consumer purchase intention, especially in the same industry. This includes what happens to ‘Malangan’ batik products, where challenges must be faced not only with local products but also with products from other countries. This study intends to determine the influence of product innovation, social media marketing, and aesthetic value on customers' purchase intentions toward ‘Malangan’ batik. The study population comprises all ‘Malangan’ batik consumers in Malang city, with an undetermined number of individuals. The accidental sampling technique was used to select respondents and gather data for this study by distributing questionnaires to the final sample size of 180 people. This research uses quantitative methods analyzed with SmartPLS-4.1.0.8. The results of this study found that continuous product innovation, effective implementation of social media marketing, and a strong emphasis on aesthetic value in products are essential strategies for businesses to significantly increase consumer purchase intention. Future studies should consider expanding the scope of the research to include additional variables that may influence consumer purchase intentions regarding ‘Malangan’ batik.